The Effect of Motivation, Discipline and Leadership on Commitment of Management: The Case of Indonesian Tenis Table Association (PTMSI) Muara Enim - Afri Yeny; Sri Rahayu; Diah Isnaini Asiati (International Journal of Business, Management and Economics, 2026)
This study aims to determine the influence of motivation, discipline, and leadership on administrators' commitment at the Indonesian Table Tennis Association (PTMSI) Muara Enim, both simultaneously and partially. The research problems in this study are to examine how motivation, discipline, and leadership simultaneously affect the commitment of PTMSI Muara Enim administrators, and how each variable partially affects their commitment. The data used in this study are primary data collected through the distribution of questionnaires to 89 PTMSI Muara Enim administrators. The analytical method employed is multiple linear regression. Before the analysis, the research instruments were tested for validity and reliability. Furthermore, classical assumption tests were conducted, including tests for normality, multicollinearity, and heteroscedasticity. The results indicate that motivation, discipline, and leadership simultaneously have a positive and significant effect on the commitment of PTMSI Muara Enim administrators. Based on the findings, motivation, discipline, and leadership, both partially and simultaneously, have a positive and significant effect on administrators' commitment at the Indonesian Table Tennis Association (PTMSI) Muara Enim. Leadership is the most dominant variable influencing administrators' commitment